A cadastral web-mapping solution for a Libyan district / Amal Omar Abdulghader S.Omar - Amal Omar Abdulghader, S.Omar (2008)
In the 21st century with the proliferation of digital data and the availability of digital map, the use of geographic information system (GIS) technique has become the best technique to develop the cadastral information system (CIS). CIS is integrated with the land register system and cadastral mapping system. The digital cadastral database (DCDB) which shows real coordinates for the cadastral maps is hampered by the many land laws in the country. This research study examines in detail the existing structure and concepts of the cadastral mapping system. A practical and functional prototype e-tool based on A Cadastral Web-Mapping Solution for a Libyan District (CW-MSLD) has been developed to assist real estate ownership registration. CW-MSLD System prototype was developed based on a pilot case study in Tripoli which is the capital city in Libya. The prototype is developed using modern GIS techniques (Web Mapping). Web Mapping techniques make maps and geoinformation available to groups of end users through a web page. The prototype tool triggers the map server software which integrates the map data stored in DCDB with the land register data stored in the MySQL database. Authorized users are able to interact with the cadastral map by using the available map tools within the system to obtain particulars pertaining to location, area and boundaries of any one parcel displayed on the map. Subsequently, the information derived can be used to register or transfer ownership for the cadastral map and further issue a cadastral certificate for the registered cadastral (real estate).